2009
DOI: 10.1017/s107407080000314x
|View full text |Cite
|
Sign up to set email alerts
|

Best Management Practices to Enhance Water Quality: Who is Adopting Them?

Abstract: This study investigates the determinants affecting producers' adoption of some Best Management Practices (BMPs). Priors about the signs of certain variables are explicitly accounted for by testing for inequality restrictions through importance sampling. Education, gender, age, and on-farm residence are found to have significant effects on the adoption of some BMPs. Farms with larger animal production are more apt to implement manure management practices, crop rotation, and riparian buffer strips. Also, farms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…These include farm size, enterprise mix, productivity per hectare, age, experience, education, off farm employment and experience of agri-environment schemes (Lynch et al, 2001;Genghini et al, 2002;Curtis and Robertson, 2003;Shultz, 2005;Troy et al, 2005;Winter et al, 2007;Ghazalian et al, 2009;Mante and Gerowitt, 2009;Yu and Belcher, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These include farm size, enterprise mix, productivity per hectare, age, experience, education, off farm employment and experience of agri-environment schemes (Lynch et al, 2001;Genghini et al, 2002;Curtis and Robertson, 2003;Shultz, 2005;Troy et al, 2005;Winter et al, 2007;Ghazalian et al, 2009;Mante and Gerowitt, 2009;Yu and Belcher, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In agricultural applications, farm size, crop types and livestock species are known to influence the scale, type and frequency of conservation practice adoption (Ghazalian et al . ). Less evidence is available about the relationship between yard attributes and practices specifically related to polluted run‐off reduction.…”
Section: Pro‐environment Behaviourmentioning
confidence: 97%
“…While the effect of age on conservation practice adoption is usually significant, it is inconsistent across a variety of conservation practice studies (reviewed in Ghazalian et al . ). Frequently, levels of environmental education and awareness can predict conservation behaviour.…”
Section: Pro‐environment Behaviourmentioning
confidence: 97%
“…Asci et al (2015) argue that the incidence of BMPs on the mean and variance of profit and farmers' attitude toward risk condition adoption. Ghazalian et al (2009) find that larger farms are more likely to adopt BMPs because they can more easily afford implementation costs 6 and are more often the object of criticism regarding the adverse effects of agricultural production. Reimer et al (2012) did in-depth interviews with Indiana farmers and found that those who care about off-farm environmental benefits and feel responsible to others are most likely to adopt BMPs.…”
Section: The Growing Influence Of Rural Residents and Bmpsmentioning
confidence: 99%
“…They are also required to have a sustainable fertilization plan prepared by an agronomist and public hearings must be held before new hog production projects can be implemented. The federal and provincial governments have also promoted the adoption of specific BMPs like crop rotations, surface runoff controls, reduced herbicide use, solid and liquid manure management with adoption rates ranging from 15% to 66% (Ghazalian et al, 2009). Government programs were underperforming in meeting sustainable development objectives and tensions between farmers and rural residents remained in spite of the additional regulations imposed on farmers (MDDEP, 2011a).…”
Section: Introductionmentioning
confidence: 99%